Sustainability and corrosion. Issue 1 (November 2021) - Atkins, Chris; Lambert, Paul
Abstract : As a part of the drive to reduce carbon dioxide emissions, embodied energy figures are under consideration for construction materials. One aspect that needs to be included is the loss of embodied energy associated with corrosion and degradation throughout the life of a structure. This paper presents a review of corrosion and protection methods from the point of view of whole-life embodied carbon. This paper presents the examples that provide the lowest embodied carbon option for different environments for steel and reinforced concrete.